Changing patterns in the burden of paediatric injuries during the COVID-19 pandemic: a study in Mozambique's central hospitals - Vanda Amado; Sebastien Trott; Jette Möller; Maria Tereza Couto; Lee Wallis; Lucie Laflamme (BMC, 2023)
Abstract Introduction There is a substantial body of knowledge on the effects of the COVID-19 pandemic on injuries showing frequent but inconsistent reductions in both volume and pattern. Yet, studies specifically addressing children are less common, not least from low- and middle-income countries. This study investigated whether changes in the pattern and outcome of paediatric injury admissions to Mozambique's four regional referral hospitals during 2020. Methods Clinical charts of paediatric patients presenting to the targeted hospitals with acute injuries were reviewed using a set of child, injury, and outcome characteristics during each of two consecutive restriction periods in 2020 using as a comparator the same periods in 2019, the year before the pandemic. Differences between 2020 and 2019 proportions for any characteristic were examined using the t-test (significance level 0.05). Results During both restriction periods, compared with the previous year, reductions in the number of injuries were noticed in nearly all aspects investigated, albeit more remarkably during the first restriction period, in particular, greater proportions of injuries in the home setting and from burns (7.2% and 11.5% respectively) and a reduced one of discharged patients (by 2.5%). Conclusion During the restrictions implemented to contend the pandemic in Mozambique in 2020, although each restriction period saw a drop in the volume of injury admissions at central hospitals, the pattern of child, injury and outcome characteristics did not change much, except for an excess of home and burn injuries in the first, more restrictive period. Whether this reflects the nature of the restrictions only or, rather, other mechanisms that came into play, individual or health systems related, remains to be determined.